Drought decreases cooperative sentinel behavior and affects vocal coordination in meerkats. (3rd July 2019) - Rauber, Ramona; Clutton-Brock, Tim H; Manser, Marta B
Abstract: Cooperative breeding often evolved in harsh and arid habitats characterized by high levels of environmental uncertainty. Most forms of cooperative behavior have energetic costs and previous studies have shown that the contributions of individuals to alloparental provisioning are conditional on their food intake. However, the effect of naturally occurring, extreme environmental conditions on the persistence of costly forms of cooperative behaviors and their coordination by communication remain unknown. Here, we show that in meerkats ( Suricata suricatta ) the probability to act as sentinel, a cooperative vigilance behavior, was the same for typically occurring dry and wet conditions, but significantly reduced during a drought condition with almost no rain, especially in young individuals, members of small groups and groups with pups. The duration an individual stayed on sentinel guard, however, was most reduced during dry conditions. Besides reductions in sentinel behavior, the vocal coordination of foraging meerkats differed when comparing drought and wet conditions. Individuals responded more strongly to playbacks of sentinel "all-clear" calls and close calls, resulting in less vigilance and more foraging behavior during the drought condition. We conclude that while meerkats are adapted to commonly occurring dry periods with low rainfall, the extreme drought period with almost no rain, led to a decrease of the frequency of costly forms of cooperative behaviors in favor of behaviors that maximize direct fitness benefits and also affected the vocal coordination among group members. Abstract : Little is known about the effect of naturally occurring extreme environmental conditions on the persistence of cooperative behaviors and their vocal coordination. Our study on meerkats shows that the probability to act as sentinel was significantly reduced during a drought year with almost no rain, compared to typical dry and wet years. Foraging meerkats also responded stronger to playbacks of sentinel 'all-clear' calls, resulting in less vigilance and more foraging behavior during the drought year.